Students' problem solving abilities: An exploratory study - Samonte, Evelyn G. (Animo Repository, 2006)
This study explored students problem solving abilities in non-routine and open-ended problems in terms of their conceptual understanding, strategies and reasoning, computation and execution, communication and insights among six sophomore students of Mater Ecclesiae School in San Pedro, Laguna during the fourth quarter of the school year 2004 – 2005. The Northwest Regional Educational Laboratory problem solving model and scoring rubric was adapted to delineate students problem solving abilities on the following aspects: conceptual understanding strategies and reasoning computation and execution communication and insights. Students were classified as either emerging, developing, proficient and exemplary in each aspect of problem solving. More so, students goal, orientation and approach were determined and described using the Table for Classifying Students Goal, Orientation and Approach. Covering a period of three weeks, the study was conducted during the students regular class hours. The design consisted of 4 phases: (1) Preliminaries (2) Orientation (3) Exposure to non – routine and open – ended problems (4) interview. Data for this study were gathered and analyzed by using four instruments: an activity sheet a problem solving scoring rubric a table for classifying students goal, orientation and approach an audio – taped interview. Results of the study revealed that students problem solving abilities in terms of conceptual understanding, strategies and reasoning, execution and computation, communication and insights vary depending on the type of problem they are solving. Students were exemplary on conceptual understanding, strategies and reasoning, computation and execution on some problems but were also developing on other aspects. They may be poor on computation, but good in finding appropriate strategy for the problem and so with the other aspects. They, too, have varying problem solving goal orientation and approach. From the analysis of the students problem solving abilities it could be inferred that students perform better in non-routine problems than in open-ended problems. Evidently, students performed better and demonstrated more open orientation in non-routine problems than in open-ended problems. Students goal in open-ended problems is directed towards more on giving an answer to the problem. Most of their work discloses that they have a restricted orientation and that their weaknesses in problem solving can be readily identified.